Biological Activity of Ethanol Extract of Terminalia chebula Dried Carp against Bacterial Wilt of Lycopersicum esculentum and its Mechanism of Inhibition - Ajith, Padmalatha; Prabha, SB (Indian Journal of Pharmaceutical Education and Research, 2024)
Background The extract of Terminalia chebula was explored with a new perspective to control tomato bacterial wilt, opening up a new way in agriculture to control plant disease in an organic way with less impact on the environment, ecosystem and consumers. Materials and Methods The preliminary study reveals the presence of phenolic compounds, coumarins and anthroquinones in the ethanol extract and was analysed further by GCMS and NMR to identify the compounds, structure and functional group in the EE. The macro-dilution superior to diffusion method to find the rate of inhibition to measure the potential of phytochemicals in Ethanol Extract (EE) Results The optimum of 0.1 mg/mL of crude EE inhibits 56% of Ralstonia solanacearum (RS) effectively up to 96% with 0.8 mg/mL. The extent of the in vitro, in vivo experiment on tomato (Lycopersicum esculentum) to check any toxic compounds in EE that hinder plant growth and the absence of such compounds makes the EE a good source of organic alternatives for synthetic compounds. Simultaneously to find biologically active compounds reduces the disease severity in the inoculated plant. The pot culture experiments were conducted with seeds and plants of Lycopersicum esculentum that received EE against induced RS infection. Conclusion The five phytochemicals in crude ethanol extract have bioactivity on host plants inoculated with Ralstonia solanacearum, the severity of the disease decreased with that of the diseased plant not receiving any treatment. The extract-treated plant was measured in height and weight to non-treated control plants and there was a significant difference between groups. Identified compound affinity was measured with molecular docking and interpreted.
Keywords: Ralstonia solanacearum; Terminalia chebula; Antibacterial activity; Macro-dilution method; Pot culture; Organic control